Self‐regulation in chemical and bio‐engineering materials for intelligent systems. Issue 1 (4th April 2018) - Huang, Zhongyuan; Lei, Kewei; He, Dan; Xu, Yanbin; Williams, Jacob; Hu, Liu; McNeil, Macy; Ruso, Juan M.; Liu, Zhen; Guo, Zhanhu; Wang, Zhe
Abstract : Herein, the authors review the self‐regulation system secured by well‐designed hybrid materials, composites, and complex system. As a broad concept, the self‐regulated material/system has been defined in a wide research field and proven to be of great interest for use in a biomedical system, mechanical system, physical system, as the fact of something such as an organisation regulating itself without intervention from external perturbation. Here, they focus on the most recent discoveries of self‐regulation phenomenon and progress in utilising the self‐regulation design. This paper concludes by examining various practical applications of the remarkable materials and systems including manipulation of the oil/water interface, cell out‐layer structure, radical activity, electron energy level, and mechanical structure of nanomaterials. From material science to bioengineering, self‐regulation proves to be not only viable, but increasingly useful in many applications. As part of intelligent engineering, self‐regulatory materials are expected to be more used as integrated intelligent components.